Evaluation of Topographical Co-Cr-Mo Alloy Surface Changes After Various Finishing Treatments - Ştefan Ţălu; Sebastian Stach; Boris Klaić; Asja Čelebić (University of Zagreb. School of Dental Medicine, 2019)
Purpose: To quantify the influence of three different finishing treatments on the cobalt-chromiummolybdenum (Co-Cr-Mo) alloy surface based on stereometric analysis parameters. Materials and methods: Eighteen specimens were casted from an extra-hard alloy (Wironit®, BEGO, Bremen, Germany). The samples were distributed into three groups (n = 6 samples per group) dependent on different polishing techniques applied, as follows: A group, only electropolished (EP) samples; B group, after EP, an additional mechanical polishing process was applied to the surface by rubber discs and a polishing paste (RP); C group, after EP, an additional mechanical polishing process was completed by rubber discs, polishing paste and finally by a rotating deer leather wheel (RPDL). Samples were imaged by atomic force microscopy (AFM) in a contact mode, in air, at room temperature. Results: The evaluation of the microtexture of the sample surface was made based on the 3-D roughness parameters. The lowest statistical surface roughness parameters were found in the RP samples, whereas the highest values were obtained from the EP samples. Conclusions: The experiments described can help manufacturers identify the most appropriate parameters and their ranges within which optimal surface characteristics can be achieved.